Influence of pectin and CMC on physical stability, turbidity loss rate, cloudiness and flavor release of orange beverage emulsion during storage - Mirhosseini H.; Tan C.P.; Aghlara A.; Hamid N.S.A.; Yusof S.; Chern B.H. (2024)
Indexed by Scopus